Hubungan stres kerja tenaga kesehatan dengan kualitas pelayanan di UPT Puskesmas Medan Sunggal - Fitria, Dilla; Salmira, Cut Saura; Meliala, Sri Agustina (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Introduction: The quality of healthcare services hospital staff provides is essential for advancing a hospital as a healthcare service provider. Work-related stress experienced by healthcare workers due to heavy workloads can impact patient care quality. This study examines the relationship between work-related stress among healthcare workers and service quality at UPT Puskesmas Medan Sunggal in 2023. Method: This study employs a quantitative research design with a cross-sectional approach. The population consists of 50 respondents, and a total sampling technique was applied, resulting in a sample size of 50 respondents. Data analysis includes univariate and bivariate analyses. Results: The chi-square statistical test revealed a significant relationship between work-related stress and service quality, with a p-value of 0.006 < α (0.05). This indicates a significant correlation between healthcare workers' stress levels and the quality of services at UPT Puskesmas Medan Sunggal in 2023. Conclusion: There is an important relationship between healthcare workers' stress levels and service quality at UPT Puskesmas Medan Sunggal. Most healthcare workers experience moderate stress (52%), while 66% of respondents express dissatisfaction with the services. The chi-square test confirms a significant association between these variables (p-value 0.006 < 0.05), highlighting the need for effective stress management strategies to improve service quality.